Astral sciences in Mesopotamia - Hunger, Hermann, 1942- (Handbook of Oriental Studies. Section 1 The Near and Middle East, 1999)
Astronomy and astrology, or the astral sciences, played an enormous, if not a key role in the political and religious life of the Ancient Near East, and, later, of the Greek and Roman world. This is the first comprehensive and up-to-date account of the origins of the astral sciences in the Ancient Near East. Every type of Sumerian or Akkadian text dealing with descriptive or mathematical astronomy, including many individual tablets are thoroughly dealt with. All aspects, such as the history of discovery, reconstruction, and interpretation come to the fore, accompanied by a full bibliography. At that the reader will find descriptions of astronomical contents, an explanation of their scientific meaning and the place a given genre or tablet has in the development of astronomy both within the Mesopotamian culture and outside of it. Because celestial omens are intimately related to astronomy in Mesopotamian science, these are also discussed extensively. The material is arranged both chronologically and thematically, so as to help make Astral Sciences in Mesopotamia a reference work on the subject in its truest sense.